2018
DOI: 10.1021/acs.jpclett.7b02679
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Stability in Perovskite Solar Cells by Assembling 2D/3D Stacking Structures

Abstract: Two-dimensional (2D) perovskites have been shown to be more stable than their three-dimensional (3D) counterparts due to the protection of the organic ligands. Herein a method is introduced to form 2D/3D stacking structures by the reaction of 3D perovskite with n-Butylamine (BA). Different from regular treatment with n-Butylammonium iodide (BAI) where 2D perovskite with various layers form, the reaction of BA with MAPbI only produce (BA)PbI, which has better protection due to more organic ligands in (BA)PbI th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
419
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(436 citation statements)
references
References 37 publications
17
419
0
Order By: Relevance
“…[32][33][34] However, the stability remains a serious issue, and researchers should pay more attention to improve CsPbI 3 black phase stability for further commercial applications. [39,40] The barrier molecules in 2D perovskite could inhibit the components decomposition, [41] phase change, [42] or oxidization, [43] when the device is exposed to ambient environment. [39,40] The barrier molecules in 2D perovskite could inhibit the components decomposition, [41] phase change, [42] or oxidization, [43] when the device is exposed to ambient environment.…”
mentioning
confidence: 99%
“…[32][33][34] However, the stability remains a serious issue, and researchers should pay more attention to improve CsPbI 3 black phase stability for further commercial applications. [39,40] The barrier molecules in 2D perovskite could inhibit the components decomposition, [41] phase change, [42] or oxidization, [43] when the device is exposed to ambient environment. [39,40] The barrier molecules in 2D perovskite could inhibit the components decomposition, [41] phase change, [42] or oxidization, [43] when the device is exposed to ambient environment.…”
mentioning
confidence: 99%
“…Organic–inorganic lead halide perovskite (PVK), with its outstanding photophysical properties and versatility in low‐temperature solution processes,1, 2, 3, 4, 5, 6, 7, 8 is considered one of the most promising materials for thin‐film solar cells 9, 10, 11. In just the few years since its invention, the power conversion efficiency (PCE) of the organic–inorganic hybrid PVK solar cell (PSC) based on mixed cations and halides has been rapidly increased to as high as 22.7% 12, 13, 14…”
mentioning
confidence: 99%
“…[10] Related research [6] have shown that the small 2D crystallites formed on top of 3D MAPbI 3 layer. [11,12] The subgap quantum efficiency (QE) spectra further support the structural similarity between pristine and target perovskites (Figure 2f). In this regard, further structural analysis was performed by X-ray diffraction (XRD) analysis.…”
mentioning
confidence: 55%